Evidence for Extending Anomalous Miocene Volcanism at the Edge of the East Antarctic Craton. Issue 7 (6th April 2018) - Licht, K. J.; Groth, T.; Townsend, J. P.; Hennessy, A. J.; Hemming, S. R.; Flood, T. P.; Studinger, M.
Abstract: Using field observations followed by petrological, geochemical, geochronological, and geophysical data, we infer the presence of a previously unknown Miocene subglacial volcanic center 230 km from the South Pole. Evidence of volcanism is from boulders of olivine‐bearing amygdaloidal/vesicular basalt and hyaloclastite deposited in a moraine in the southern Transantarctic Mountains. 40 Ar/ 39 Ar ages from five specimens plus U‐Pb ages of detrital zircon from glacial till indicate igneous activity 25–17 Ma. The likely source of the volcanism is a circular −735 nT magnetic anomaly 60 km upflow from the sampling site. Subaqueous textures of the volcanics indicate eruption beneath ice or into water at the margin of an ice mass during the early Miocene. These rocks record the southernmost Cenozoic volcanism in Antarctica and expand the known extent of the oldest lavas associated with West Antarctic Rift system. They may be an expression of lithospheric foundering beneath the southern Transantarctic Mountains. Plain Language Summary: Little is known about the geology of Antarctica's ice‐covered interior, so unexpected volcanic rocks collected from Earth's southernmost glacial moraine provide valuable insights about what is under some of that ice. Analysis of five samples shows that volcanism occurred 20.6–17 million years ago, likely under Antarctica's early ice sheet. The source was a volcanic center only 230 km from the South Pole and 400 km from the nearest tectonic boundary. The volcanic source was identified from a geophysical survey that shows a circular magnetic anomaly 60 km upstream from the moraine where the cobbles were found. In addition to these volcanic rocks, three sand‐sized zircon crystals were found in glacial sediments and are 25–19 million years old. These are the youngest zircon grains ever found in the Transantarctic Mountains and also indicate igneous activity. It is unusual to have such volcanism and igneous activity within a plate. Recent work has identified a reversal in Earth's layers here that brings warm rocks, normally deeper in the Earth, closer to the surface. Our samples provide physical evidence in support of this otherwise inaccessible anomaly. Key Points: Olivine basalt, hyaloclastite erratics, and detrital zircon at Earth's southernmost moraine (Mount Howe) indicate magmatic activity 25–17 Ma The source, indicated by a magnetic anomaly (‐740 nT) 400 km inland from the West Antarctic Rift margin, expands the extent of Miocene lavas Data corroborate lithospheric foundering beneath the southern Transantarctic Mountains based on location of volcanism (duration <5 my)